Review of the rodent paleoparasitological knowledge from South America - Beltrame, Maria Ornela (2014)
Rodents (Mammalia, Rodentia) are a key mammalian group with a worldwide distribution. The relevance of rodents as hosts in parasitic life-cycles, also in those of zoonotic impact, has been fully recognized. Parasites have been found in ancient remains throughout the world. Paleoparasitology is the study of ancient parasites recovered from archaeological and paleontological sites and materials. This paper reviews the major research activities carried out in rodent paleoparasitology from South America, aiming to integrate data and generate prospects in this field of research. The presence of rodent parasites in ancient times can provide useful and valuable information, as rodent paleoparasitological data can be used from diverse point of views. Anthropologists, biologists, archaeologists, and paleontologists can use this data to reconstruct ancient events based on the parasite life cycles and on the biological requirements to maintain the transmission from host to host. Rodent paleoparasitology may provide a picture of the biodiversity of parasites in ancient times. Although rodent remains are generally present in ancient times, their recovery from archaeological and paleontological contexts is still exceptional.